Testing Multi-Factor Models in ADRs: Emerging Market vs. Developed Market - Que, Tingting; Mok, Wai Yin; Cheung, Kit Yee (International Journal of Accounting & Finance Review, 2020)
This paper tests whether the Carhart four-factor model and the Fama-French five-factor model can explain variation in returns of 1,230 ADRs originating from six developed markets and five emerging markets. We aim to compare emerging market ADRs with developed market ADRs in terms of traditional risk factors significance, model fitness and the existence of abnormal returns. Overall, we find that substantial variations exist among ADRs by their origin-of-market. First, both models show that most of the positive abnormal returns we document accrue to emerging market ADRs, mainly Chinese ADRs. Among the risk factors, market risk premium is found to be most prevalent in both emerging and developed markets. Although we find some difference in the presence of particular risk factors employed in the four-factor vs. five-factor model, overall, there are no significant differences in the explanation power between the two models. Lastly, the low R2 values imply that both models do not work very well with the international market ADRs.